Histochemical Dynamics of Ovarian Tissue across Developmental Stages in sheep - Mir Shabbir Ahmad; Massarat Khan; Masuood Ahmad John; A.R.Choudhury; S.A.Shah (Indian Journal of Veterinary Anatomy, 2026)
Seasonal variation had no appreciable effect on histochemical reactions; however, clear age-related differences were observed. Neutral mucopolysaccharides (PAS-positive substances) showed generally weak reactions in prepubertal animals, increasing to mild–moderate intensity in pubertal and adult groups, particularly in follicular components, zona pellucida, corpus luteum, and stroma. Glycogen content was uniformly low or absent across most ovarian structures, irrespective of age. Acid mucopolysaccharides exhibited mild to moderate reactivity in stromal tissue, follicular layers, basement membrane, zona pellucida, and follicular fluid, with comparatively higher activity in developing and tertiary follicles. Basic proteins were consistently present in most ovarian structures with moderate to strong reactions in granulosa cells, basement membranes and zona pellucida of growing follicles. Lipids and phospholipids showed mild to moderate distribution in follicular cells, luteal tissue, and stroma with relatively higher lipid content in prepubertal ovaries and a decreasing trend with advancing age.